Regeneration of Hair Cells in the Human Vestibular System - Huang, Yikang; Mao, Huanyu; Chen, Yan (Frontiers in Molecular Neuroscience, 2022)
The vestibular system is a critical part of the human balance system, malfunction of this system will lead to balance disorders, such as vertigo. Mammalian vestibular hair cells, the mechanical receptors for vestibular function, are sensitive to ototoxic drugs and virus infection, and have a limited restorative capacity after damage. Considering that no artificial device can be used to replace vestibular hair cells, promoting vestibular hair cell regeneration is an ideal way for vestibular function recovery. In this manuscript, the development of human vestibular hair cells during the whole embryonic stage and the latest research on human vestibular hair cell regeneration is summarized. The limitations of current studies are emphasized and future directions are discussed.